THE QUALITY SERVICE FOR PATIENTS OF BPJS WITH ANTENATAL PATIENTS SATISFACTION IN THE COMMUNITY HEALTH CENTERS IN TEGAL CITY - Meyliya Qudriani; Nilatul Izah; Nora Rahmanindar (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
The Social Insurance Administration Organization or known as BPJS is one form of social protection to ensure the community in order to realize the provision of health insurance and meet the health needs of the community. To realize the 1945 Constitution, article 28 and Law no. 36 of 2009, the government must provide health services that are equitable, fair, and affordable for the people of Indonesia. In the service of pregnant women patients will get satisfaction in the service at the health center both independently and in collaboration, therefore every pregnant woman needs to require at least four visits during the antenatal period, namely one visit during the first trimester, one visit during the second trimester and two times visit during the third trimester. The purpose of this study was to determine the quality of BPJS patient services with antenatal care patient satisfaction at the Community Health Center in Tegal City. The study design was descriptive-analytic with the cross-sectional approach. The population in this study were all pregnant women in the Community Health Center in Tegal City in July 2019. The sampling technique used in this study was the accidental sampling technique, with the total sample obtained was 70 respondents. The results of this study are the characteristics of respondents about BPJS ownership obtained; all respondents already have BPJS (100%), most respondents were at the gestational age 4-6 months gestation (42.9%), and most respondents were multipara (61.4%). The satisfaction of pregnant women in terms of tangibility, reliability, assurance, responsiveness, and empathy, most respondents were satisfied with ANC services at the Community Health Center in Tegal City.Keywords: BPJS, antenatal care, quality